DUKUNGAN ORANG TUA TERHADAP PRESTASI ATLET RENANG JAWA BARAT - Syarfuddin, Stabit (2015)
Sports is an activity to train human, not only physically but also spiritually. Swimming is one of the sports recognized by Indonesian people. This is proven by the inclusion swimming in various sports championship. The deciding factors in optimum achievements in sports can be classified/grouped in 4 aspects i.e: biological, psychological, enviromental, & supporting aspects. Based on the description above, it can be concluded that: in athlete's achievement, there are 4 contributing factors that are 1) Biological Aspects comprise potential or body's basic ability, body organs' functions, body stature, & nutrients. 2) Psychological aspects comprise intellectuality, motivation, personality, & movement coordination. 3) Environmental aspects comprise social, facilities and infrastructures, & weather or climates. 4) Supporting aspects comprise coach, training program, & award/bonus. Therefore it is suggested for athletes who want maximum achievements to pay attention to four aspects above. Based on the result of the research, calculation, and data analysis, author can conclude that the aspects mentioned are showing contributions to swimming athletes as big as 77%. This means every support parents give during training or match heavily influences athlete's achievements, while the rest 23% is decided by other factors, such as intelligence, the ability to control emotion, and the athlete's maturity itself. *Student's Research of Sports Coaching Education Department, FPOK UPI, Class of 2011.